Diklat Penjaga Jalur Lintasan Kereta Api sebagai Edukasi Keselamatan Perkeretaapian kepada Masyarakat Sumatera Barat - Handoko Handoko; Akbar Zulkarnain; Dimas Adi Perwira (Edujavare Publishing, 2024)
Level crossings are always a complex problem because accidents often occur at level crossings, whether at official or unofficial level crossings, guarded or unguarded. This community service aims to provide education, insight, and knowledge about railroad crossings to the people of West Sumatra. The method used in this activity is Community Based Research (CBR) by applying approach. This community service was carried out through face-to-face learning and practice in the field, which was attended by 26 people. The result of this service is that the people of West Sumatra increasingly understand and realize the importance of safety at level crossings. This training is very useful because initially the training participants did not know about safety at level crossings, but after attending the training the participants gained very significant knowledge and experience, including being able to know several things about level crossings, starting from regulations, rules and regulations at level crossings and level crossing managers. In this way, the people of West Sumatra, especially training participants, know safety at railway level crossings and understand how to handle emergency conditions at railway level crossings.